Legal Protection for The Owner of Warung Makan Ibu Gambreng Trademark: A Study of Supreme Court Decision No. 988 K/Pdt.Sus-HKI/2024 - Baransano, Jeremia; Tarina, Dwi Desi Yayi (Jurnal Daulat Hukum, 2025)
This study meticulously analyzes the legal protection afforded to the owner of the prior registered trademark “Warung Makan Ibu Gambreng,” focusing on the landmark Supreme Court Decision Number 988 K/Pdt.Sus-HKI/2024. The research holds two primary objectives: first, to thoroughly examine the consistency and efficacy of legal protection under the Indonesian Law No. 20 of 2016 concerning Marks and Geographical Indications, and second, to dissect the detailed legal considerations and judicial reasoning that led the Supreme Court, as the Judex Juris, to decisively cancel the competing mark, “Nasi Gambreng Bu Esti.” The research utilizes a Normative Legal Research methodology, primarily employing the Case Approach focused on the specific decision, the Statute Approach analyzing the relevant trademark law, and the Conceptual Approach to interpret key legal principles. Data collection relies exclusively on secondary sources, including primary legal materials (the Supreme Court Decision) and secondary legal materials (academic journals, books, and articles), all subjected to Qualitative Content Analysis for critical interpretation. The findings reveal a significant and correctable discrepancy between the Commercial Court, which initially rejected the lawsuit based on formalistic visual differences, and the Supreme Court. The MA decisively established the defendant to have acted in bad faith, thereby overriding the Judex Facti’s restrictive formal approach, as the foundation for cancellation was the Defendant's proven misappropriation of the Plaintiff's goodwill established through the prior franchise agreement. The novelty of this research lies in its specific analysis of this Supreme Court judgment, which sets a crucial precedent: the abuse of an established contractual business relationship, such as a franchise, is confirmed as compelling and decisive evidence of bad faith under Article 21 paragraph (3), thereby significantly reinforcing the prioritization of substantive justice and ethical business conduct in Indonesian trademark law.